PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VI UPT SPF SDN SIPALA II MAKASSAR - Amiruddin, Nurkhalisah; Hastati, , Sri; Nurhidayah, A. Resky (ALENA : Journal of Elementary Education, 2023)
This study aims to (1) determine student learning styles (2) the effect of learning styles on student learning outcomes. The research method used is quantitative ex-post facto type. The research location took place at UPT SPF SDN Sipala II Makassar, with the research sample being class VI students, totaling 19 students. The instruments used are questionnaires and documentation. The data in this study were analyzed using statistical analysis. Based on the research that has been done, the results are (1) the kinesthetic learning style is 42.10% for 8 students, the visual learning style is 36.85% for 7 students, and the auditory learning style is 21.05% for 4 students (2) the results of hypothesis testing show that there is no effect of learning styles on student learning outcomes. This is evidenced by the results of the t-test compared to t-table (dk 17), namely 1.634 <1.740. And a significance value of 0.121 > 0.05.